Children with Developmental Verbal Dyspraxia: Changes in articulation and perceived resilience with intensive multimodal intervention. (October 2016) - Martin, Maureen K; Wright, Lindsay Elizabeth; Perry, Susan; Cornett, Daphne; Schraeder, Missy; Johnson, James T
Research into intervention strategies for developmental verbal dyspraxia (DVD) clearly demonstrates the need to identify effective interventions. The goals of this study were to examine changes in articulation skills following the use of phonetic, multimodal intervention and to consider the relationship between these improved articulation skills and perceptions of resilience behaviors. These changes were related to components of the World Health Organization (WHO) International Classification of Functioning, Disability, and Health, Children and Youth version (ICF-CY). The intervention was implemented daily for 12 children diagnosed with DVD, ages 3 to 10 years, enrolled in a school for children with speech, language, and hearing impairments on a university campus in the southeast of the USA. Eleven children presented with significant comorbid conditions. Changes in articulation, along with changes in parents' and speech-language therapists' (SLTs') perceptions of resilience behaviors were measured. At the end of a 2-year period, statistically significant gains in articulation and parents' and SLTs' perceptions of resilience behaviors were noted. The relationship between improved articulation skills and increased resilience behaviors is discussed.